STUDI SEMIOTIKA TENTANG STRATEGI BRAND STORYTELLING DALAM MEMBANGUN BRAND IMAGE DAN BRAND EQUITY PADA INDUSTRI SKINCARE - Farida, Ayu; Azhar, Andi (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
This study aims to analyze how the brand storytelling strategy employed by the skincare brand Wardah influences brand image and the formation of brand equity. The research adopts a qualitative descriptive method, utilizing Roland Barthes' semiotic analysis to examine the denotative and connotative meanings in advertisements. The study focuses on how visual, verbal, and narrative signs used in brand storytelling strategies shape consumer perceptions of skincare brands. The findings indicate that semiotic elements such as colors, symbols, language, and narratives play a crucial role in creating a strong brand image and enhancing brand equity. This research also reveals that storytelling aligned with relevant values can strengthen the emotional bond between the brand and consumers, positively impacting consumer loyalty. Additionally, the advertisements emphasize that beauty comes from within-not only in terms of physical appearance but also in the form of self-confidence and personal comfort. Keywords: Semiotic Study, Brand Storytelling, Brand Image, and Brand Equity